Intensive Care Unit Nurses' Uncertainty and Patient Safety Culture (International Journal of Studies in Nursing, 2018)
Intensive care unit (ICU) nurses face many uncertain situations that may affect their patient care decisions and jeopardize patients’ safety. Aim: This study aimed to explore the relationship between uncertainty and patient safety culture among intensive care unit nurses at Tanta Main University Hospital. Study subject: included (155) nurses worked in intensive care units at Tanta University Main Hospital. Two tools were used Tool (I): Nurses’ Uncertainty Questionnaire. Tool (II): Patient Safety Culture Questionnaire. Results: 74.2% of participant ICU nurses’ experienced high levels of uncertainty. Above half (56.1% and 56.1%) of them always experienced being uncomfortable and confused& loss of control when facing uncertain situations in ICUs. 84.5% and 76.8% of them always used team work; and learn from past experience to deal with uncertainty. 47.1% of them evaluated patient safety in their ICUs as acceptable and bad. There was a high statistical negative correlation between the levels of patient safety culture and experiencing uncertainty by ICU nurses at p= 0.000. Conclusions: ICU nurses experienced high level of uncertainty; they rely on experience and teamwork rather than evidence-based practices to manage clinical uncertainty. High statistical significant negative correlation was found between patient safety culture and experiencing uncertainty by ICU nurses.